Detailed flow development and indicators of transition in a natural convection flow in a vertical channel. (November 2019) - Thebault, Martin; Giroux-Julien, Stéphanie; Timchenko, Victoria; Ménézo, Christophe; Reizes, John
Highlights: Transitional natural convection is studied experimentally and numerically. Different transition indicators are defined based on velocity and thermal quantities. Detailed experimental and numerical mapping of the flow spatial development is provided. Realistic environmental conditions are considered. Abstract: A spatially developing transitional flow in a vertical channel with one side heated uniformly and subjected to random velocity fluctuations at the inlet is investigated in this experimental and numerical study. Two Rayleigh numbers are studied. Experimentally, Particle Image Velocimetry is used to obtain a complete two-dimensional velocity field of the streamwise flow development. A three-dimensional Large-Eddy-Simulation investigation is also performed to obtain a complete streamwise evolution of the flow. The results allow the definition of three transition indicators on the basis of the time-averaged velocities and temperatures fields as well as on the turbulent statistics of the flow. The detailed experimental and numerical spatial development of the transitional natural convective flow is then presented and the ability of the indicators to capture the early and the advanced stages of the transition is assessed. The numerical simulations were performed on the assumptions of a thermally stratified environment, submitted to an environmental noise, and for which wall to wall radiations were considered. These conditions aim at representing realistic experimental conditions.